2011
DOI: 10.1111/j.1471-0528.2010.02880.x
|View full text |Cite
|
Sign up to set email alerts
|

Malaria in pregnancy: the difficulties in measuring birthweight

Abstract: Recommendations for interventions to control malaria in pregnancy are often based on studies using birthweight as the primary endpoint. Differences in birthweight may be attributable partly to methodological difficulties. We performed a structured search of the literature using ‘malaria’, ‘pregnancy’ and ‘birth weight’ as search terms. Of the clinical trials reporting birthweight, only 33% (14/43) gave information about the timing of the measurement and details on the scales used. Seventy seven per cent explai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 99 publications
(221 reference statements)
1
44
2
Order By: Relevance
“…This clinic is based on the western border of Thailand where malaria transmission is low and seasonal; P. falciparum and P. vivax are the predominant species. All pregnant women routinely have a dating ultrasound scan at their first antenatal clinic (ANC) attendance (26) and are invited to attend the frequent (weekly) screening program to detect and treat all malaria episodes (22) and prevent maternal mortality (28). Women receive ferrous sulfate and folic acid supplements from the first ANC consultation until delivery.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This clinic is based on the western border of Thailand where malaria transmission is low and seasonal; P. falciparum and P. vivax are the predominant species. All pregnant women routinely have a dating ultrasound scan at their first antenatal clinic (ANC) attendance (26) and are invited to attend the frequent (weekly) screening program to detect and treat all malaria episodes (22) and prevent maternal mortality (28). Women receive ferrous sulfate and folic acid supplements from the first ANC consultation until delivery.…”
Section: Methodsmentioning
confidence: 99%
“…Blood samples (2 ml) were obtained from a catheter inserted in a vein and were taken into 1-ml lithium heparin tubes (for PPQ) and 1-ml prechilled sodium fluoride-potassium oxalate tubes (for DHA) at baseline (before the first dose) and at hours 0.5, 1.5, 4, 8 (before the 2nd dose), 24.5, 25.5, 28, and 32 (before the third dose), and 48.25, 48.5, 49, 50, 51, 52, 54, 56, 60, and 72. The catheter was removed, and additional samples were taken for PPQ by venous puncture at days 5,7,14,21,28,35,42,49,56,63,77, and 84. Wholeblood samples for PPQ drug concentrations were centrifuged at room temperature at 1,500 to 2,000 ϫ g for 10 min to obtain plasma.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…91 Gestational age estimation is notoriously diffi cult in resource-poor settings. In the studies shown in fi gure 3, neither ultrasound dating (early gestation ultrasound is the gold standard for gestational age estimation) nor fetal size charts to diagnose intrauterine growth restriction were available.…”
Section: Eff Ect On Fetuses and Infantsmentioning
confidence: 99%
“…In the studies shown in fi gure 3, neither ultrasound dating (early gestation ultrasound is the gold standard for gestational age estimation) nor fetal size charts to diagnose intrauterine growth restriction were available. 91 Fetal distress (measured by cardiotocography or meconium staining of the amniotic fl uid) is an important feature of symptomatic falciparum malaria and severe anaemia, both before and during labour. 62,79 In areas where women attend antenatal clinics late in pregnancy or only for delivery, miscarriage rates are probably underestimated.…”
Section: Eff Ect On Fetuses and Infantsmentioning
confidence: 99%